ANALISIS PENGENDALIAN INTERN SIKLUS PERSEDIAAN DAN PENGGUDANGAN PADA PT. SAPTA SARI TAMA - Powa, Yudhi; Nangoi, Grace; Walandouw, Stanley Kho (Universitas Sam Ratulangi, 2018)
PT. Sapta Sari Tama is a national company engaged in the distribution of medicines (pharmacy). Because there are quite a number of types of products and mobility in and out of goods so that the problems that are feared will occur, namely the physical difference between the inventory available in warehouse and the amount recorded in the inventory, loss or theft of goods stock, as a result, internal control of the inventory and warehousing cycles is needed so as not to occur fraud in carrying out the task. The purpose of this study was to determine whether the internal control of the inventory and warehousing cycles at PT. Sapta Sari Tama is sufficient. The method used in this study is a type of qualitative research presented in descriptive form. While data collection techniques are carried out by direct survey to PT. Sapta Sari Tama and interviewed several resource persons in the company. From the results of the study as a whole, internal control of the inventory and warehousing cycles is quite effective, where the company's management has implemented the concepts and principles of internal control. This is in accordance with the Regulation of Financial Accounting Standards (PSAK) No. 14 about inventory.Keywords : Analysis, Internal Control, Inventory, Warehousing, PSAK No. 14